My fangtastically evil vampire pet eaudiobook - O'Hara, Mo (My Fangtastically Evil Vampire Pet, 2018)
My FANGtastically Evil Vampire Pet, the epic spin-off of Mo O'Hara's New York Times bestselling My Big Fat Zombie Goldfish series features an aspiring evil scientist, paranormal pets, and plenty of hilarious summer camp shenanigans. Welcome to Camp Mwhaaa-haa-ha-a-watha! This summer is going to be epic. Epically evil, that is. 'Cause I'm going to Evil Scientist Summer Camp! No annoying little brothers. No annoying zombie goldfish. Just me, my best friend Sanj, our notebook of evil plans, and my truly evil (and totally forbidden) vampire kitten Fang. We've got it all planned out. Okay, so maybe I didn't expect for the totally not-evil Geeky Girl to show up, or for Sanj to find a new partner to work with, but there's no way I'm going to let them ruin my summer. Evil Emperor of the Camp, here I come! Signed, The Great and Powerful Mark